(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The main aim of the study was to investigate the effectiveness of the academic performance of 9th standard students after applying self regulated instructional model. The sample of the study consisted of 80 students of 9th standard Vijayapur city. The investigator selected the stratified random sampling technique. The objective of the study is to find out the academic performance of the 9th students of Vijayapur city after applying self regulated instructional Model. Also to find the effect of the self regulated instructional Model in academic performance. The result revealed that there is a significant relation between the self regulated instructional Model and in academic performance.